TOWARDS A NEW PROCEDURE TO SET UP GROUNDWATER THRESHOLD VALUES IN ACCORDANCE WITH THE PREVISIONS OF THE EC DIRECTIVE 2006/118: A CASE STUDY FROM ACHAIA AND CORINTHIA (GREECE) - Christoforidou, P.; Panagopoulos, A.; Voudouris, K. (Bulletin of the Geological Society of Greece, 2010)
The EU Water Framework and Groundwater Directives stipulate that EU member states have to assess groundwater chemical status by the use of groundwater threshold values derived for the protection of dependent ecosystems and human health. In the EU’s 6th FP BRIDGE project ‘‘Background cRiteria for the IDentification of Groundwater thrEsholds’’, a methodology for the derivation of threshold values (TV) for groundwater bodies is proposed. Threshold values are quality standards for polluting substances in groundwater that need to be formulated by the Member States for the status assessment of groundwater bodies. These values represent the concentration of a pollutant that cannot be exceeded in order to protect both the environment and human health. The proposed method derives groundwater threshold values based on environmental objectives for groundwater ”itself” as a receptor, using relevant reference criteria such as natural background levels, drinking and irrigation water standards. This methodology is tested on seven districts in Greece (two of them are analyzed in this paper). Concentrations of major ions, ammonium and data of electrical conductivity were examined. After a pre-selection on databases with groundwater samples the natural background level is determined as the 90- and 97.7 percentile.